PUSTAKA SANDI KLASIK BERBASIS COMPONENT OBJECT MODEL (COM) - Amin, M. Miftakul (Jurnal Informatika, 2014)
Security and confidentiality are important issues that need serious attention in the era of information technology. Cryptography is one technique for securing data and information. In cryptography, the data is disguised in such a way that even if the data can be read, it can not be understood by those who do not have the authority. Data that has not undergone encoding known as The term plaintext, and after camouflaged with an encryption method, then it will turn plaintext into ciphertext. In general, a system equipped with a password to restrict only certain parties were entitled to enter into the system. If the password can be solved or known by an unauthorized person, then the data or information that is in the system is threatened. This research aims to develop a library classical password that can be used as an attempt to realize the aspect of information security in access control, by utilizing the technology component object model (COM). From the results of tests performed can be seen that the COM libraries are packed in COM DDL can be used by a variety of programming languages fairly easily.Keywordsâ cryptography, component object model (COM)